Effect of planting distances and Humic Acid application on some vegetative growth and yield of Broad bean (Vicia faba L. var. Somar) in outdoor condition - Meerza, Chnar Hama noori; Marif, Arsalan Azeez; Majeed, Ardalan Jalal (Kurdistan Journal of Applied Research, 2018)
The seeds of the Somar variety (local production) were planted in mid of October (after being soaked with water for 16 hours) in panels 1.5 x 2 meters. Broad bean (Vicia faba var. Somar) was studied in outdoor to determine the effect of three planting distances (20, 25 and 30 cm), four different Humic Acid (HA) concentration doses (zero, 1.5, 3.0 and 4.5) ml / liter H2O, with three replicates on some of the plant’s vegetative and yield traits; Plant Height (cm), Plant Diffusion (cm), Number of Branches /Plant, Number of Flowers / Plant, Number of Pods / Plant, % percentage of Pods Set, Total Pods Yield /plant (gm), Pod Weight (gm). The (HA) were added by spray way directly to the top of the soil with two applications, the first after 3 weeks from complete germination, while the second after branching immediately. The experiment was designed as Randomized Complete Block Design (RCBD). Based on Total pods yield / plant (gm), the best interaction between the plant distance and different concentration of (HA) was a combination of the planting distance 30 cm, and treated the soil with 3.0 ml/ literH2O.